Joint passive time reversal and multichannel equalization for underwater communications - Gomes, João (2006)
Time reversal has aroused considerable interest in communications applications as a means of partially compensating for the intersymbol interference introduced by the channel. This paper presents experimental results for a passive time reversal experiment conducted off the west coast of Portugal during the MREA’2004 mission. A single acoustic projector generated a 2/4-PSK stream at 200 and 400 baud, modulated around a carrier frequency of 3600 Hz. The signals were received at a range of about 2 Km from the source on a sparse vertical array with 8 hydrophones. We examine several strategies for demodulating the data, including equalization, time-reversal, and combinations of both techniques. This work emphasizes the use of low-complexity multichannel combining algorithms for tracking channel variations prior to generating a passively focused signal.